'Poverty's scar: A qualitative inquiry of financing shortcomings in specialized burn hospitals. Issue 5 (August 2021) - Amini-Rarani, Mostafa; Mohammadi, Farzaneh; Shaarbafchizadeh, Nasrin; Yazdi-Feyzabadi, Vahid
Highlights: Beside deadly risks, individuals with lower socioeconomic status have more financial problems in paying SBH bills. For revenue generation, it is suggested to concentrate on seeking new financial resources through advocacy and earmarked taxes. Burn-care insurance coverage has shortcomings that affect the breadth, depth, and height of the burn care coverage. It would be helpful to allocate financial resources based on supply and demand objective indicators rather than politicized actions. All individuals should take care of preventive measures for protection against burn injuries and related financial problems. Abstract: Background: Victims of burn have particular characteristics such as high vulnerability, expensive treatment, and cost of burn services. Thus, the financing of burn services is crucially important. The purpose of the present work is to recognize the financing challenges in Iranian specialized burn hospitals (SBHs). Methods: In the present qualitative descriptive research, purposive sampling was used for selecting key informants with maximum variation at local, provincial, and national levels. Semi-structured interviews were used for data collection. Interviews were continued as long as the saturation point was achieved at the 21 st interview. We employed conventional content analysis using an inductive data-driven coding process and theme development for the analysis of the transcribed documents by MAXQDA Analytics Pro 2018 (VERBI GmbH Release 18.2.0 Berlin). Results: We extracted 3 themes and 12 sub-themes, including resource mobilization (the poor burnt victims, unique feature of the single- SBH, high direct and indirect costs, and poor intra-sectoral advocacy), insurance coverage for burn care (incomplete breadth of population coverage, inadequate depth of benefits package and coverage of costs, and reimbursements of burn care) and mechanism of financial resource allocation (unsuitable payment system, less sustainable budgeting, inappropriate tariffing for burning services, top-down budgeting approach, and politicized budget process). Conclusions: We suggest that health policy-makers in Iran could modify the SBHs financing system by improving resource mobilization, scaling up insurance coverage for burns, and optimizing the allocation of financial resources. Besides, we propose several points for policy entry to address SBHs financial difficulties. These points are serious attention to vulnerable and the poor burn patients, provision of burn care in multi-specialized hospitals, strengthening intra-collaboration, revision of tariffs, and payments for burn services, and preservation and realization of burn budgeting.